Antidiabetic Activity of Peperomia pellucida In Streptozotocin-Induced Diabetic Mice - Hidayati, Sholihatil (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2021)
Background: Diabetes mellitus is a heterogeneous group of diseases in the form of disorders in the body's metabolism clinically. Peperomia pellucida herbs have phytochemical containing which is antidiabetic potential development. Objectives: This study was conducted to compare the antidiabetic activity of ethanol extract and n-hexane fraction of Peperomia pellucida. Material and Methods: This research was conducted by make diabetic mice with 50 mg/kg.bw of streptozotocin induction, which was then treated with ethanol extract and n-hexane fraction of Peperomia pellucida with doses 250 mg/kgbw for 7 days. Results: The results showed that the ethanol extract and n-hexane fraction of Peperomia pellucida reduced blood glucose levels in diabetic mice due to streptozotocin induction. The n-hexane fraction of Peperomia pellucida can lower blood glucose levels as much 244.00 Â± 18.99 mg/dL better than the ethanol extract, which is 99.50 Â± 28.17 mg/dL. Conclusions: Peperomia pellucida herb has the potential to be developed as an antidiabetic agent.